Measurement and Analysis of the Impact of Oil Revenues on Imports in Iraq (2004-2021) - Lazkin, Rozan; Hussain, Abdul Razzaq (Humanities Journal of University of Zakho, 2023)
This study dealt with the relationship between the imports and the oil revenues in Iraq from 2004 to 2021 by studying and analyzing these variables. The main aims of this study are: identify the nature of the Iraqi imports and the extent of their dependence on oil revenues, explain the shortcomings in the economic policy, especially the commercial, as oil exports constitute 95% of the total Iraqi exports, analyze the growth of the Iraqi imports, as well as oil revenues and their role in the Iraqi economy and measure the impact of oil revenues on the imports. The study hypothesizes that there is a fundamental dependence on oil revenues in funding the imports in the Iraqi economy, which in turn affects the conditions of oil demand in the foreign market, and thus its import capacity corresponds to the trends of its revenues. The results show that during 2004-2021 the imports are clearly consistent with the oil revenues, as the increase or decrease in the revenues affects the imports in the same direction, especially from the consumer side. Besides, there is a financial dominance of oil revenues over the Iraqi economy as they constitute 95% of the public revenues. They are considered the main factor for financing the Iraqi federal general budget resulting in a unilateral economy. Additionally, there is a lack of a clear-cut trade policy and dominance of the consumer pattern. The Iraqi economy is unilateral in terms of export and diversified in imports. Nowadays, the Iraqi market imports most of its needs from abroad and this affected the local production and removed much of it from the circle of competition.